Two Novel Mutations in ABHD12: Expansion of the Mutation Spectrum in PHARC and Assessment of Their Functional Effects - Chen, Dong-Hui; Naydenov, Alipi; Blankman, Jacqueline L.; Mefford, Heather C.; Davis, Marie; Sul, Youngmee; Barloon, A. Samuel; Bonkowski, Emily; Wolff, John; Matsushita, Mark; Smith, Corrine; Cravatt, Benjamin F.; et al. (Human mutation, 2013)
ABSTRACT PHARC (polyneuropathy, hearing loss, ataxia, retinitis pigmentosa, and cataracts) is a recently described autosomal‐recessive neurodegenerative disease caused by mutations in the α−β−hydrolase domain‐containing 12 gene (ABHD12). Only five homozygous ABHD12 mutations have been reported and the pathogenesis of PHARC remains unclear. We evaluated a woman who manifested short stature as well as the typical features of PHARC. Sequence analysis of ABHD12 revealed a novel heterozygous c.1129A>T (p.Lys377*) mutation. Targeted comparative genomic hybridization detected a 59‐kb deletion that encompasses exon 1 of ABHD12 and exons 1–4 of an adjacent gene, GINS1, and includes the promoters of both genes. The heterozygous deletion was also carried by the patient's asymptomatic mother. Quantitative reverse transcription‐PCR demonstrated ∼50% decreased expression of ABHD12 RNA in lymphoblastoid cell lines from both individuals. Activity‐based protein profiling of serine hydrolases revealed absence of ABHD12 hydrolase activity in the patient and 50% reduction in her mother. This is the first report of compound heterozygosity in PHARC and the first study to describe how a mutation might affect ABHD12 expression and function. The possible involvement of haploinsufficiency for GINS1, a DNA replication complex protein, in the short stature of the patient and her mother requires further studies. We identified two novel mutations in ABHD12 in a woman with PHARC, a heterozygous p.Lys377* mutation and a 59‐kb deletion that encompasses exon 1 of ABHD12, exons 1‐4 of GINS1, and the promoters of both genes. In this first functional study of the effect of ABHD12 mutations, we demonstrated a 50% decrease in ABHD12 RNA expression and absence of ABHD12 hydrolase activity. Haploinsufficiency for GINS may play a role in the short stature of the patient and her mother.